The HPV-16 E7 oncoprotein induces centriole multiplication through deregulation of Polo-like kinase 4 expression - Korzeniewski, Nina; Treat, Benjamin; Duensing, Stefan (Molecular cancer, 2011)
Infection with high-risk human papillomaviruses (HPVs) such as HPV-16 is intimately associated with squamous cell carcinomas (SCCs) of the anogenital tract and a subset of oropharyngeal carcinomas. Such lesions, including pre-invasive precursors, frequently show multipolar mitoses and aneuploidy. The high-risk HPV-16-encoded E7 oncoprotein has been shown to rapidly induce centrosome abnormalities thereby causing the formation of supernumerary mitotic spindle poles and increasing the risk for chromosome missegregation. HPV-16 E7 has been found to rapidly induce centriole overduplication, in part, through the simultaneous formation of more than one daughter centriole at single maternal centrioles (centriole multiplication). The precise molecular mechanism that underlies HPV-16 E7-induced centriole multiplication, however, remains poorly understood.
Gesehen am 07.07.2022